JARINGAN SOSIAL DALAM MENJALANKAN AKTIVITAS MAKE UP ARTIST (MUA) PADA MAHASISWA DI KOTA PEKANBARU - Dewi Kurniawati; Indrawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The makeup artist is an artist who has the ability to make makeup in other people’s body parts, including the face. These skills and abilities are derived from a beauty class or the privates of a makeup professional. As a hobby of profession, make up artist in the Pekanbaru City of fair is now deeply concerned by various students, because this activity doesn’t take much time and is running at any time. This phenomenon about activity in the world of makeup is what research is all about. The main focus on this writing leads to social networks. There are forms of tissue, an interest network, a sentimental network, and a power network, ini which all three networks are formed of mutually beneficial relationships. Data retrieval is made by observation following the student activities of the Pekanbaru City that run activities as make up artist and interviews in depth and documenting. Interviews conducted where reseachers verbally and direcly question the subject in full effect. It’s inconceivable that being a make up artist is not an easy ting to do, because it takes a desire to continue learning to sharpen the skills of make up, a lot of money to buy makeup, and mentally strong to take criticism from a client. Keywords : Make Up Artist (MUA), Activity and Social Network.